Influence of the bracing scheme on seismic performances of MRF-EBF dual systems. (May 2017) - Montuori, R.; Nastri, E.; Piluso, V.
Abstract: The work herein presented has the aim to investigate the influence of the bracing scheme on the seismic performances of Moment Resisting Frames-Eccentrically Braced Frames (MRF-EBF) dual systems, designed according to two design approaches: the first one is the Theory of Plastic Mechanism Control (TPMC) while the second one is based on Eurocode 8 (EC8) design provisions. Even though TPMC design approach is not introduced in modern seismic codes, it has earned the reputation of being a robust design approach because of its strong theoretical background, based on the kinematic theorem of plastic collapse extended to the collapse mechanism equilibrium curve to assure a collapse mechanism of global type. Conversely, the design approach based on EC8 promotes the application of the so-called beam-column hierarchy criterion which is usually able to avoid soft-storey mechanisms but does not assure the yielding of all the dissipative zones, because a collapse mechanism of global type is very rarely attained. The main purpose of the present work is to compare, given the above mentioned design approaches, the different seismic performances resulting from the use of the four different bracing scheme proposed by codes. For this reason, 5 bay buildings with 4, 6 and 8 storeys have been examined considering four bracing schemes providing a total number of 12 structural schemes analyzed. The seismic performances have been evaluated by means of Incremental Dynamic Analyses (IDA) carried out until the achievement of structural collapse and repeated for a set of ten earthquake ground motion. Highlights: Influence of the bracing scheme on the seismic performances of (MRF-EBF) dual systems has been investigated. Two design approaches: Theory of Plastic Mechanism Control (TPMC) and Eurocode 8 (EC8) design provisions have been applied. IDA analyses have been carried out on a number of MRF-EBF dual systems for a set of ten earthquake ground motion. The bracing scheme showing the best performances have been found.